Peran Media Sosial Instagram dalam Meningkatkan Brand Engagement di Instagram Monochrome - Andhika Putra Riyadi, Rhama; Genep Sukendro, Gregorius (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Monochrome is a local brand operating in the fashion sector. In running the company since 2010, Monochrome has implemented marketing communications as a method or form of sales, the use of social media in the form of seeking brand engagement, and CRM as a form of maintaining relationships with customers. In practice, this communication is continuous with one another. Social media is used as a forum for seeking brand engagement through entertainment content which is executed by content creators and proposed ideas and concepts by social media specialists, then it will continue to marketing communications in selling Monochrome products and building relationships with customers through CRM. This research uses a qualitative approach with a case study method. Data collection was carried out by researchers by means of observation, interviews and documentation. In increasing brand engagement, Monochrome uses social media specialists to create marketing strategies through Instagram social media. This is proven by the way social media specialists create and promote idea concepts that content creators will execute. In executing this content, the content creator will create entertainment or educational videos in search of brand engagement and also CRM as a form of maintaining relationships with customers. Monochrome merupakan brand lokal yang bergerak di bidang fashion. Dalam menjalankan perusahaan sejak 2010, Monochrome menerapkan komunikasi pemasaran sebagai cara atau bentuk penjualan, pemanfaatan media sosial dalam bentuk mencari brand engagement, dan CRM sebagai bentuk menjaga hubungan dengan pelanggan. Dalam pelaksanaannya, komunikasi ini saling berkesinambungan antara satu dengan lainnya. Sosial media dijadikan wadah mencari brand engagement melalui konten entertainment yang di eksekusi oleh content creator dan diusung ide dan konsep oleh social media specialist, kemudian akan berlanjut kepada komunikasi pemasaran dalam menjual produk Monochrome dan membangun hubungan dengan pelanggan melalui CRM. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Pengumpulan data dilakukan peneliti dengan cara observasi, wawancara, dan dokumentasi. Dalam meningkatkan brand engagement, Monochrome menggunakan social media specialist dalam membuat strategi pemasaran melalui media sosial Instagram, hal ini terbukti dengan cara social media specialist membuat dan mengusung konsep ide yang akan dieksekusi content creator. Dalam mengeksekusi konten tersebut, content creator akan membuat video entertainment atau pun edukatif dalam mencari brand engagement dan juga CRM sebagai bentuk dalam menjaga hubungan dengan pelanggan.